1993
DOI: 10.1007/bf00932254
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofSchistosoma haematobium soluble egg antigens that elicit human granuloma formation in vitro

Abstract: Schistosoma haematobium soluble egg antigens (SH SEAs) induce intense granulomas in human hosts that often culminate in severe disease. In an attempt to identify the SH SEA fractions that are responsible for pathology, we combined T-cell Western blotting and an in vitro model of granuloma formation. Whole SH SEAs were dotted onto nitrocellulose pieces or were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and electrotransferred onto nitrocellulose paper. Horizontal strips bearing the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Also these results somehow came in line with the results obtained by Hillyer and Pacheco (1986) who demonstrated six distinct bands with MW of 131, 76, 74, 55, 40 and 25 kDa on analyzing the protein components of S. haematobium adult worm antigen preparation. Concerning the bands obtained for S. haematobium SEA were came in line with Gaafar et al (1993) who revealed seven bands ranged from 84 to 28 kDa namely, 84, 63, 57, 55, 40, 30 and 28 kDa. While Mahfouz et al (2011) detected bands ranged from 106-18.5 kDa.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Also these results somehow came in line with the results obtained by Hillyer and Pacheco (1986) who demonstrated six distinct bands with MW of 131, 76, 74, 55, 40 and 25 kDa on analyzing the protein components of S. haematobium adult worm antigen preparation. Concerning the bands obtained for S. haematobium SEA were came in line with Gaafar et al (1993) who revealed seven bands ranged from 84 to 28 kDa namely, 84, 63, 57, 55, 40, 30 and 28 kDa. While Mahfouz et al (2011) detected bands ranged from 106-18.5 kDa.…”
Section: Discussionsupporting
confidence: 61%
“…USA). Molecular mass of both the SDS-PAGE and western-blot was determined using GelProAnalyzer package (Media Cybernetica;1993). Both expirements were repeated three times.…”
Section: Western Blotting or Immunoelectroblottingmentioning
confidence: 99%
“…The unexcreted schistosome egg, in contrast, may persist for many years in host tissues and is a well-established, potent immunogen (e.g., soluble egg antigen or SEA [69]). Indeed, the systemic and granulomatous immune response to urogenital schistosomiasis is primarily driven by egg-associated antigens [70], [71]. Our model has methodologic similarities to synchronous granuloma formation induced by bolus injection of eggs into the mouse tail, cecal, or portal vein [64], [72], [73].…”
Section: Discussionmentioning
confidence: 99%
“…2-Cys peroxiredoxin [34] (H- 104 RKQEISKAYGVFDE EDGNA 122 -OH)-derived peptide, showing lowest homology to the murine counterpart, was synthesized as a tetra branched multiple antigen peptide (MAP) construct and purified at AnaSpec, Inc. (San Jose, California). Schistosoma mansoni soluble egg antigen (SEA) was prepared as described [35].…”
Section: Methodsmentioning
confidence: 99%